The Effect of Mall Atmosphere, Brand Image, and Visitor Satisfaction on Return Intention at Living World Denpasar - Ni Komang Sarmila; Ni Wayan Sri Suprapti (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study aims to explain the influence of mall atmosphere, brand image, and visitor satisfaction on the intention to revisit Living World Denpasar. The intention to revisit is the result of various factors involving previous experiences and the hope of getting the same or even better experience on the next visit. The population of this study was the people of Denpasar City who had visited Living World Denpasar. Data were collected through a direct survey from 120 visitors who were taken purposively from the population and then analyzed using descriptive statistics and inferential statistics in the form of multiple linear regression. The results showed that mall atmosphere , brand image, and satisfaction have a positive influence on the intention to revisit. The results showed that the better the mall atmosphere, the better the brand image, and the more satisfied the visitors were, the three would increase the intention of visitors to revisit Living World Denpasar.